Hydroxytyrosyl Eicosapentaenoate as a Potential Antioxidant for Omega-3 Fatty Acids: Improved Synthesis and Comparative Evaluation with Other Natural Antioxidants. - García-Acosta, Natalia; Cert, Rosa; Jordán, Marta; Goya, Luis; Mateos, Raquel; Espartero, Jose Luis (Biomolecules, 2025)
Hydroxytyrosol (HT), the primary phenolic compound in virgin olive oil, has notable cardiovascular benefits, particularly in preventing low-density lipoprotein (LDL) oxidation. However, its hydrophilicity limits its solubility and integration into lipid-based formulations. This study aimed to enhance its lipophilicity by synthesizing hydroxytyrosyl eicosapentaenoate (HT-EPA), a derivative of HT and eicosapentaenoic acid (EPA), using a one-step enzymatic catalysis with lipase B from Candida antarctica (CALB). The reaction, performed as a suspension of HT in ethyl eicosapentaenoate (Et-EPA) (1:9 molar ratio) under vacuum, achieved higher yields and shorter reaction times than previously reported, with a purity exceeding 98%, confirmed by 1H-NMR. For the first time, the antioxidant capacity of HT-EPA in comparison with other natural antioxidants was assessed using the FRAP assay, while its oxidative stability in an omega-3-rich oil matrix was evaluated via the Rancimat method. HT-EPA and hydroxytyrosyl acetate (HT-Ac) displayed antioxidant activity comparable to HT but significantly higher than α-tocopherol, a common food antioxidant. Given the scarcity of effective lipid-soluble antioxidants, HT-EPA represents a promising candidate for omega-3 nutraceuticals, offering enhanced stability and potential health benefits. This study provides a simple, efficient, and scalable strategy for developing functional lipid-based formulations with cardioprotective potential by improving HT solubility while preserving its antioxidant properties.